Об одном из методов оценивания показателей надежности газотранспортных систем - Набатова, С. Н.; Мамедова, А. А. (ХНУРЭ, 2008)
In the given work the problem of the analysis of reliability of compressor station, in particular, the approach to an estimation of indicators of reliability is considered. Use of the structurally logic scheme of reliability TS that allows to solve both a direct (to define reliability depending on time and a reservation method) and return (to define time or a method of reservation depending on reliability) problem of reliability is offered LS. Thus, the considered approach is practically applicable for a wide range of problems.
Keywords: надежность газотранспортных систем; оценивание показателей надежности